2017
DOI: 10.1002/dta.2168
|View full text |Cite
|
Sign up to set email alerts
|

Thirteen years of the fight against doping in figures

Abstract: Every year, the World Anti-Doping Agency (WADA) publishes the main statistics reported by the accredited laboratories, which provide very valuable information for assessing changes in the patterns of doping in sports over time. Using the information provided since 2003 as the basis for the analysis, the evolution of doping/anti-doping figures over the last decade can be examined in reasonable detail, at least in reference to samples analyzed and categories of substances more commonly found in athletes' samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 11 publications
2
19
0
Order By: Relevance
“…Studies placed in SRP employed four different methods for determining prevalence, which were Direct Survey (DS) , Random Response Technique (RT) [102][103][104][105][106][107][108][109][110], Qualitative Interviews (QI) [111], and Network Scale Up (NS) [55]. Studies placed in SAP employed four different methods for determining prevalence, which were Testing Figures (TF) [112][113][114][115][116][117][118][119][120][121], Blood Profile (BP) [122][123][124], Anti-Doping Rule Violations (AD) [125][126][127], and Hair Sample (HS) [79]. One study [79] was found to use a method assigned to SRP and to SAP, thus it was included in both with its two assessment scores included independently in Electronic Supplementary Material Appendix S4.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Studies placed in SRP employed four different methods for determining prevalence, which were Direct Survey (DS) , Random Response Technique (RT) [102][103][104][105][106][107][108][109][110], Qualitative Interviews (QI) [111], and Network Scale Up (NS) [55]. Studies placed in SAP employed four different methods for determining prevalence, which were Testing Figures (TF) [112][113][114][115][116][117][118][119][120][121], Blood Profile (BP) [122][123][124], Anti-Doping Rule Violations (AD) [125][126][127], and Hair Sample (HS) [79]. One study [79] was found to use a method assigned to SRP and to SAP, thus it was included in both with its two assessment scores included independently in Electronic Supplementary Material Appendix S4.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…The World Anti‐Doping Agency (WADA) annually publishes a list in which prohibited drugs are organized into twelve classes and the three forbidden methods of chemical and physical manipulation, gene doping, and the manipulation of blood and blood components . The number of drugs deemed as “prohibited” has dramatically increased over the decades, which has led to increased demands for stricter anti‐doping policies and control methods . In light of these demands for more control, class‐dependent or multi‐class approaches for analysis have evolved over the years.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the substantial body of evidence concerning adverse effects of pseudo‐endogenous and synthetic anabolic‐androgenic steroid (AAS) misuse at, for example, the cardiovascular, renal, and hepatic levels, statistics regarding AAFs continue to list AAS as the most frequent reason of drug‐related anti‐doping rule violations (ADRVs) . This highlights the importance of anti‐doping research in this field.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Over the last 13 years, the number of doping controls has increased resulting in growing numbers of adverse analytical findings (AAFs). Remarkably, however, the percentage of atypical findings and AAFs has remained within the range of 1–2% . Despite positive developments enabling enhanced, large‐scale testing in general (ie, increased overall test numbers, decreased costs/sample, decreased administrative expenditures, etc.…”
Section: Introductionmentioning
confidence: 99%